New pathways for governing food system transformations: a pluralistic practice-based futures approach using visioning, back-casting, and serious gaming - Mangnus, Astrid C; Vervoort, Joost M.; McGreevy, Steven R; Ota, Kazuhiko; Rupprecht, Christoph DD; Oga, Momoe; Kobayashi, Mai (Resilience Alliance, Inc., 2019)
The global environmental change that characterizes the Anthropocene poses a threat to food systems. Cities increasingly serve as the spaces where civil society, private actors, and local governments come together to strategize toward more sustainable food futures and experiment with new forms of food governance. However, much of the futures literature in the context of sustainability focuses on large-scale, global scenarios. These are important pieces of knowledge, but they often do not effect a change in local perspectives and practices. In this paper we respond to the need for novel futures approaches to help urban coalitions of societal actors create pathways to sustainability transformations. We investigate how existing examples of good practices, or “seeds,” can be used to open up novel, desirable, bottom-up futures in the case study of Kyoto (Japan). Innovative combinations of methodologies (visioning, back-casting, simulation games) are used and assessed in order to create multiple ways of experimenting and engaging with food system futures. Our results consist of a pluriform pathway to a sustainable Kyoto food system. Each method brings in its unique pathway elements: visioning to formulate a desired end goal, back-casting to create a step-by-step action plan, and gaming to practice with the future. The combination of Kyoto-based “seeds” with initiatives from elsewhere and with a new food system governance model (a food policy council) resulted in participants learning about new food system practices, extending their networks, and support for actualizing a food policy council. We conclude that multimethod futures processes that combine existing practices and new modes of governance are a promising new way to outline various pathways for sustainability transformations.